What (de)motivates gen Z women and gen Z men at work? Comparative study of gender differences in the young generation’s motivation - Lašáková, Anna; Vojteková, Monika; Procházková, Lenka (Journal of Business Economics and Management, 2023)
This study responds to the call for a more nuanced understanding of intragenerational variations and provides a detailed insight into how men and women in Generation Z perceive work motivation. Unlike most prior studies with a similar focus, this study is qualitative, employing a specific method of empathy-based stories (MEBS) to capture the (de)motivators in Gen Z directly through their native point of view. On a sample of 437 business students, the vast majority of whom reported having work experience, results reveal that Gen Z women pay significantly more attention to social aspects of interpersonal relationships at the workplace, intrinsic factors of having a dream job, low levels of routine, experiencing job success, and an extrinsic need to receive recognition for the work done, while Gen Z men are more attentive to the altruistic factor of making a meaningful difference at work, extrinsic factor of benefits, and leisure-related aspects of happy personal life and no stress at work. Findings inform evidence-based motivation policies, which may help target more precisely recruitment and motivation programs in companies.